Three treatises - Luther, Martin (Fortress Press, 1970)
These three treatises of 1520 are the heart of Luther's protest against the church of his day: "The Christian nobility of the German nation", "The Babylonian capivity of the Church", "The freedom of the Christian". They are about convictions causing conflict within both Protestantism and Catholicism today: the ethical responsabilities of the individual; trust in God versus trust in man's abilities; and what the freedom of the individual person means